SAMPLE DISTRIBUTION OF AGRICULTURAL STATISTICS: A CASE STUDY IN SOUTHEASTERN BRAZIL - PINO, Francisco Alberto (Brazilian Journal of Biometrics, 2017)
<span style="color: black; font-family: ’Times New Roman’,’serif’; font-size: 12pt; mso-bidi-font-size: 9.0pt; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">The probability distributions of some agricultural variables, namely planted or cultivated area, number of plants, plant stand (number of plants per hectare), production and productivity or yield (production per hectare), were studied and characterized, using census data. The hypothesis of normality was rejected for all variables and all cultivations. The main transformation to normality showed to be the logarithmic, followed by root transformations. An archetypal distribution was suggested for planted area: defined for non-negative values, heavy tail at right, mean > median > mode. It is shown to be relevant for planted area itself (91% of the cases), number of plants (87%) and production (85%), a little less for plant stand (60%) and yield (48%).